Reimagining Healthcare Equity: Advocating for Inclusion of Septorhinoplasty under Ayushman Bharat PMJAY - Bali, Kulbhushan; Kulkarni, Annarao; Das, Deepthy; MohanS, Nidhi; Mallekavu, Phaneendra (Indian Journal of Community Health, 2024)
Septo-rhinoplasty, commonly known as nose reshaping surgery, has long been associated with cosmetic enhancements in urban centers. However, it's crucial to recognize the transformative impact Septo-rhinoplasty can have in rural India, extending beyond aesthetics to address significant health and social aspects. In rural areas, where access to specialized medical care is limited, individuals often bear the physical and psychological burdens of nasal deformities without recourse. Congenital anomalies, trauma, and functional impairments due to a misshapen nose can adversely affect a person's quality of life. Septo-rhinoplasty emerges as a beacon of hope, offering not just cosmetic improvements but substantial functional benefits.